Pembentukan Persepsi Ancaman Keamanan Manusia Bagi Pengungsi Berdasarkan Tindakan Kekerasan Anti-Imigran di Jerman - Winda Noviana; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2018)
The rise of anti-immigrant acts and violence that happened at the peak of the 2015European refugee crisis became the background of this research. The emerging problem ishow’s the role of anti-immigrant behaviors in creating the threat perceptions to humansecurity for refugees in Germany by 2015 ? The purpose of this research was to providethe overview of refugee crisis, describing the anti-immigrant behaviors addressed torefugees, and explaining the relations between anti-immigrant behaviors in shaping thethreat perceptions to human security for refugees. The efforts to answer the problem andresearch’s objectives conducted by using simbolic interactionism theory, securitization andhuman security concept. The objects of this research was refugees and asylum seekersresiding in Germany during the peak of the refugee crisis in 2015. The results show thatanti-immigrant behaviors evolves with the rising amount of refugees whom have enteredGermany. Those behaviors had a role in shaping refugees’ threat perceptions throughinteraction and understanding of behaviors which later influencing the human securityindicators for refugees.